Equivalent thermal diffusivity of natural and recycled aggregate concrete at temperature up to 350 ⁰C - Izabela Hager; Katarzyna Mróz; Tomasz Tracz; Václav Kočí; Lukáš Fiala (Acta Polytechnica CTU Proceedings)
The paper presents the evolution of equivalent thermal diffusivity with temperature of concretes with natural coarse aggregates and recycled concrete aggregates. Thermal diffusivity was evaluated based on the temperature measurements made on cylindrical samples using so-called "inverse technique". Thermal diffusivity parameter was estimated for concretes manufactured with different replacement ratios of natural by recycled coarse aggregate (0, 50 and 100 %) produced by crushing the worn-out concrete pavement that was dismounted after exploitation period. The diffusivity of concrete was tested up to 350 ◦C. The progressive decrease of thermal diffusivity was observed, and the lowest D values were obtained for higher recycled concrete aggregates content. The results were presented against the background of other authors results and referred to the D values proposed in EUROCODE 2.